The thief lord - Funke, Cornelia (Chicken House Frome, 2003)
Winter has come early to Venice. Two orphaned children are on the run, hiding among the crumbling canals and misty alleyways of the city. Befriended by a gang of street children and their mysterious leader, the Thief Lord, they shelter in a disused cinema. On their trail is a bungling detective, obsessed with disguises and the health of his pet tortoises. But a greater threat to the boys' new-found freedom is a magical treasure from their forgotten past - with the power to spin time itself